(untitled) (Global Journal of Medical Research, 2014)
Diabetes Mellitus (DM) is a metabolic disorder which is greatly prevalent in Bangladesh and the use of traditional medicinal plants for its treatment is also very popular. In this study, a survey to identify the medicinal plants used for the treatment of DM in the urban areas of Dhaka and Khulna, Bangladesh was conducted. In this survey, 100 randomly chosen individuals of both Dhaka and Khulna, 50 each, were interviewed in a structured manner, regarding the use of antidiabetic medicinal plants. A total of 30 medicinal plants belonging to 18 families were accounted for the treatment of DM in Bangladesh. The most widely mentioned plants were, Coccinia indica (Telachuka), Azadirachta indica (Neem), Trigonella foenum-graecum (Methi), Syzygium cumini (Jam), Terminalia chebula (Horituki), Ficus racemosa (Joiggi dumur), Momordica charantia (Korolla), Swietenia mahagoni (Mahogany)., Phyllanthus emblica (Amloki), Terminalia bellirica (Bohera), Tinospora cordifolia (Gulancha lota), Lagerstroemia speciosa (Jarul), Withania somnifera (Aswagandha). Although a large number of traditional medicinal plants are being used for the treatment of DM in Bangladesh, extensive clinical intervention studies are essential prior to recommend their use to ensure proper public health outcomes.